Structural ordering, morphology and optical properties of amorphous AlxIn1-xN thin films grown by plasma-assisted dual source reactive evaporation - Alizadeh, M.; Ganesh, V.; Mehdipour, H.; Nazarudin, N.F.F.; Goh, B.T.; Shuhaimi, A.; Rahman, S.A. (Elsevier, 2015)
Amorphous aluminum indium nitride (AlxIn1-xN) thin films were deposited on quartz substrates by plasma-assisted dual source reactive evaporation system. In-rich (x = 0.10 and 0.18) and Al-rich (x = 0.60 and 0.64) films were prepared by simply varying an AC voltage applied to indium wire. The X-ray-diffraction patterns revealed a small broad peak assigned to Al0.10In0.90N (002) plane, but no perceivable peaks assigned to crystalline AlxIn1-xN were observed for the films with x = 0.18, 0.60 and 0.64. The morphology of the film was changed from clusters of small grains to uniformly shaped particles with decrease of x. The band gap energy of the films increased from 1.08 eV to 2.50 eV as the Al composition varied from 0.1 to 0.64. Also, Raman results indicated that E-2(high) and A(1)(LO) peaks of the AlxIn1-xN films are remarkably blue-shifted by increasing x and the A(1)(LO) phonon mode of the Al-rich films exhibits two-mode behavior. A bowing parameter of 4.3 eV was obtained for AlInN films. The extrapolated value from bowing equation was 0.85 eV for band gap energy of InN. (C) 2015 Elsevier B.V. All rights reserved.